The possibility of using e-learning tools for the development of the cognitive activity of students - T. A. Chernykh; Yu. A. Rubtsova (Открытое образование (Москва))
The process of informatization of education has led to the wide use of modern information technologies in the learning process. E-learning tools not only complement the educational process, but also become an integral part to increase efficiency and learning outcome. E-learning tools are the means to increase the interest of students to study the subject and improve cognitive activity.The success of studying at the University is related to the cognitive activity of students and is in direct relationship with it. Modern society makes demands on graduates of higher educational institutions: a high level of professional and general education, the ability to solve complex political, scientific, technical, social and economic issues. The development of cognitive activity is an indispensable element of personal growth and development, a fundamental condition for continuing education. Attempts by teachers to activate cognitive activity by increasing the volume of material, provided for study and the intensity of its filing lead to a significant decrease in the quality of education, to an increase in its stress for all subjects of the educational process. The traditional system of monitoring and evaluating the knowledge of students often introduces a contradiction in the motivational sphere of the educational process [1].Educational motivation provides the highest level of cognitive activity achieved through the student’s continuous motivation for selfimprovement, provided that the necessary conditions are created in the educational process of the higher educational institution, and also the students’ desire to achieve new results that would be higher than the results of the previous stage of learning and the results of cognitive activity.The aim of the study is to explore the possibilities of using e-learning tools in the educational process of higher educational institutions for the development of cognitive activity of students. The main approaches to the development of cognitive activity have been studied. The model of employment with the use of e-learning tools, directed on development of cognitive activity of students, is offered. Basic research methods: analysis of scientific and methodological literature and modeling.This study led to the conclusion that the development of cognitive activity of students on the basis of the use in the educational process of e-learning tools due to personalization and differentiation of the learning process, interspersing finding items and game situations, solving problems, building a personal training path. E-learning tools not only increase interest in the subject, but also involve more sense organs of students, due to which the effectiveness of mastering knowledge increases. It is necessary to use the opportunities of new information technologies not only to support traditional forms of education, but also to implement the ideas of developing education, to intensify all stages of the educational process, to prepare students for professional activities in the information society.We should note that e-learning tools could not be considered as universal tool that can solve all the didactic problems that arise in the educational process of the university. The desired result can only be achieved by fully considering the effectiveness of the use of electronic means of instruction at each stage of the learning process.